2006
DOI: 10.1080/00423110600869974
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of motorcycle models for the evaluation of the handling performances

Abstract: In this work. three motorcycle models of increased accuracy are presented. They were developed as a tool for investigating how the level of accuracy, for example. in the front kinematics, affects the handling judgment, as obtained on the basis of some handling indexes taken from the technical literature, in some typical manoeuvres. A simple driver model was also employed, which, by controlling the steering torque and the longitudinal force, makes the vehicle to follow a desired trajectory at a constant forward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Because of purposes of research, driving tasks, personal feeling ,environmental conditions and other factors, vehicle handling performance test become complicated and evaluation about handling performance can not be unified. Research in this area has a lot [3,4]. According to tested vehicles and different test conditions research applied different mathematical models, evaluation, experimental methods and experimental means.…”
Section: Test Project and Resultsmentioning
confidence: 99%
“…Because of purposes of research, driving tasks, personal feeling ,environmental conditions and other factors, vehicle handling performance test become complicated and evaluation about handling performance can not be unified. Research in this area has a lot [3,4]. According to tested vehicles and different test conditions research applied different mathematical models, evaluation, experimental methods and experimental means.…”
Section: Test Project and Resultsmentioning
confidence: 99%
“…As a result, they can estimate that the motorcycle consumes approximately 70% of the fuel (Aeeraja et al 2012). Obviously, this cannot be eliminated or drastically reduced, but a small reduction in one motorcycle will have a significant impact on the overall fuel consumption of the same model across the country (Frendo et al 2006). Tom Austin's tips for achieving higher fuel economy for the motorcycle are mentioned below (Haval et al 2012):…”
Section: Effects Of Fuel Consumptionmentioning
confidence: 99%
“…To research the level of detail necessary in motorcycle models to predict handling Frendo et al [16] investigated the differences in handling indexes with three levels of model detail and compared to literature. They found that a non-linear tire model greatly influences the results.…”
Section: Steady Turningmentioning
confidence: 99%